Self-represented witnessing: the use of social media by asylum seekers in Australia's offshore immigration detention centres. (May 2018) - Rae, Maria; Holman, Rosa; Nethery, Amy
The act of witnessing connects audiences with distant suffering. But what happens when bearing witness becomes severely restricted? External parties, including the mainstream news media, are constrained from accessing Australia's offshore immigration detention centres. The effect is that people seeking asylum are hidden from the public and excluded from national debates. Some detainees have adopted social media as a platform to communicate their stories of flight, and their experiences of immigration detention, to a wider audience. This article examines the ways in which social media, and particularly Facebook, has facilitated what we call self-represented witnessing. We analyse two public Facebook pages to assess how detainees use such social media networks to document their experiences, and we observe the interaction between detainees, other social media users and mainstream media. Significantly, these social media networks enable detained asylum seekers to conduct an unmediated form of self-represented witnessing that exposes human rights abuses and documents justice claims.